Indonesian Students’ Numeracy Skills Based On PISA Mathematical Problems In Secondary School: A Meta-Synthesis - Marhami, Marhami; Juandi, Dadang; Dasari, Dadan (Jurnal Pendidikan MIPA, 2024)
Abstract: Objectives: This study aimed to describe the Indonesian students’ numeracy skills in secondary school in solving PISA mathematical problems based on four contents namely space and shape, change and relationships, quantity, uncertainty and data. Methods: A meta-synthesis was used in this study. The final 18 articles used in this study which were published in national and international journals in 2016 to 2023, obtained from databases in Publish or Perish software. This entire articles use descriptive qualitative research that describes the numeracy abilities of Indonesian students in solving PISA model questions. The included studies were structured using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 flow diagram and analyzed using Braun & Clarke's six-step thematic analysis. Finding: The results of this study indicate that overall Indonesian students in secondary school still have difficulties in using mathematical operation, understanding problems, using strategies, and interpreting the results of solving the PISA model questions in terms of space and shape, change and relationships, quantity, uncertainty, and data content. Conclusion: Numeracy skills are fundamental for students to navigate and solve problems effectively, especially in assessments like PISA. Teachers were recommended to frequently provide non-routine problems like the PISA model, which can explore students' numeracy skills, so that students become accustomed to solving high-level problems and their numeracy skills also improve.         Keywords: numeracy skills, PISA mathematical problems, and meta-synthesis. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp14-26